ANALISIS DAN PERBANDINGAN STEGANOGRAFI PADA MEDIA AUDIO DAN GAMBAR MENGGUNAKAN LSB DAN RC4 - Ashari, Ilham Firman; Siwi, lkhsanudin Raka; Londata, Hafizh; Wicaksono, Ihtiandiko (P3M Politeknik Negeri Banjarmasin, 2023)
In the current digital era, it is deemed essential to ensure security and confidentiality of information when exchanging information through communication networks. This is done to allow recipients to receive the information from senders in its entirety without any interference from third parties who are not entitled to the information. Cryptography and Steganography are some useful methods to secure a confidential message, including the RC4 algorithm as one type of applicable method to secure the original message into a random secret message to make it remain unknown to others. One of the methods used in steganography to secure messages, including images, audio, video, and documents, is the least significant bit (LSB) algorithm. This study aims to analyze the comparison of the two-storage media, namely audio and images using LSB and RC4 in order to see the effect of the LSB and RC4 algorithms on the container media based on the aspects of imperceptibility, fidelity, recovery, and capacity. Having tested the imperceptibility aspect as indicated by the histogram of the image and the audio spectrum, it is clear that there is no difference between the image and audio before and after insertion. The fidelity test of the PSNR (Peak Signal to Noise Ration) resulted in an average value of > 30 dB, while the recovery test shows 100% success because there is no difference between the original message and after extraction. The capacity test indicates that the larger the size of the container media, the larger the message that can be inserted.